Augmentation of degradation prospects of dioxygenases from the crude extract of an efficient bacterial strain, using pyrene as sole carbon source. (2020) - Kaur, Bineypreet; Kaur, Jaspreet; Gupta, Bulbul
Abstract: In recent times, microorganisms have been screened, contemplating their potential to produce various enzymes of domestic as well as industrial importance. These enzymes possess substantial propensity for the bioremediation of carcinogenic and toxic aromatic contaminants. Catechol 1, 2-dioxygenase as well as catechol 2, 3-dioxygenase, familiar dioxygenases, are involved in specialized pathways known as meta- or ortho- cleavage pathway for the degradation of polycyclic aromatic hydrocarbons (PAHs). This report emphasizes characterization of one of the microbial strains, BJ5, adapted for higher production of catechol 1, 2-dioxygenase and catechol 2, 3-dioxygenase, using pyrene as the sole carbon source. The functionality of these enzymes is critically regulated by factors such as environmental state, pH, temperature and metal ions. Hence, in this study, specific activities, kinetic constants, pH and temperature optima were determined. These dioxygenase enzymes from the crude extract of BJ5 strain can act as alternative green catalysts for bioremediation resolution.